Indigenous‐Led Analysis of Important Subsistence Species Response to Resource Extraction - Kathleen A. Carroll; Fabian Grey; Nicholas Anderson; Nelson Anderson; Jason T. Fisher (Ecology and Evolution)
ABSTRACT Subsistence hunting, or “country food,” on traditional territories is essential for numerous Indigenous Peoples who face food insecurity. For many First Nations of Canada, subsistence hunting is also inextricably linked to traditional conservation practices, as hunting is an important way of engaging with nature. In Canada's boreal forest, large game such as moose (Alces alces) is a primary source of protein. However, resource extraction—including forestry and oil and gas—has shifted large game distributions and affected the availability and abundance of food resources. Here, the Indigenous authors designed the study and processed remote camera trap data, then sought out Western scientists to generate generalized linear models to evaluate moose habitat use and spatial‐numerical responses to possible stressors in north‐central Alberta, including fire, harvest, oil and gas extraction, and other disturbances. Together, through the coproduction of knowledge, we examined the effects of human‐caused stressors on moose habitat use by sex and age class. The proportion of various land cover types and human land use for resource extraction was important in moose habitat use. Notably, male, female, and young moose all used habitat differently and at different spatial scales. However, young moose (with their mothers) strongly selected natural forest disturbances such as burned areas but avoided human‐created disturbances such as petroleum exploration “seismic” lines. Female moose with young attempts to maximize forage opportunities do not use human‐disturbed forests in the same ways they use naturally disturbed areas. Our findings, in the context of Indigenous interpretation from remote cameras and community insights, have linked human disturbance to declines in moose densities and displacement from traditional hunting grounds. Evaluating and predicting shifts in large game distributions is critical to supporting Indigenous food security and sovereignty and identifying where industries operating on First Nations lands can better engage responsibly with First Nations.